Biosynthesis of silver and platinum nanoparticles using orange peel extract: characterisation and applications. Issue 5 (1st October 2015) - Castro, Laura; Blázquez, María Luisa; González, Felisa; Muñoz, Jesús Ángel; Ballester, Antonio
Abstract : This study focuses on the green synthesis of noble metal nanoparticles (silver (Ag) and platinum (Pt)) and how the size and shape of the nanoparticles produced can be controlled through changes in the initial pH value of the precursor solution. The nanoparticles were characterised by ultra‐violet‐visible spectroscopy, transmission electron microscopy and X‐ray diffraction. This simple and environmentally friendly method allows the synthesis of diverse nanostructures in the absence of a surfactant or polymer to direct nanoparticle growth, and without externally adding seed crystallites. The antibacterial effects of Ag nanoparticles and catalytic properties of Pt nanoparticles were explored for future promising biotechnological approaches in different fields.